Analisis Penggunaan Teknologi Informasi dan Komunikasi Untuk Pelaporan Informasi Lembaga Amil Zakat (Studi Kasus LAZ di Pekalongan) - Pratomo Cahyo Kurniawan; Tri Nurhidayah; Devi Nur Azizah (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2021)
The Amil Zakat Institution (LAZ) in its development of digital technology is expectedto provide accountability and transparency which includes presenting non-financialand financial information through information technology, namely using internetmedia. This study aims to describe the use of the internet in the form of websitesand social media in reporting information by LAZ in Pekalongan. Method researchapproach used in this research is descriptive qualitative research. The object of theresearch is the LAZ website and social media in Pekalongan. The way of collectingdata is collected by the method of documentation and observation. Then, the datawas analyzed by content analysis. The results of the research analysis show thatthe LAZs include LAZ Alummah, LAZIS MU Pekalongan, LAZIS NU Pekalongan andLAZ Central Java have used websites and social media well, websites and socialmedia are used for internet reporting, namely non-financial information. Thewebsite is used to convey organizational profiles, product information and otherimportant information that can be useful for donors or muzakki. Social media hasnot been used actively on twitter, facebook but on social media instagram andyoutube it has been used actively. In short, interaction with muzakki through socialmedia needs to be done as much as possible or enhanced by LAZ.